1980
DOI: 10.1902/jop.1980.51.4.206
|View full text |Cite
|
Sign up to set email alerts
|

Familial Benign Chronic Neutropenia Associated With Periodontal Disease: A Case Report

Abstract: A rare case report of periodontal disease associated with familial benign chronic neutropenia is presented. The medical, dental and family histories as well as clinical and histologic observations are described and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…Not all neutropenias result in periodontal disease. Familial benign chronic neutropenia has variable expressivity and although several individuals within a family may be neutropenic, not all are affected by recurrent infections or periodontal disease (34). These findings might be explained by the variable genetic expression of the disorder or by the variable effects of the environment (such as plaque or smoking) on these patients.…”
Section: Evidence For the Role Of Genetic Variants In Periodontitismentioning
confidence: 99%
“…Not all neutropenias result in periodontal disease. Familial benign chronic neutropenia has variable expressivity and although several individuals within a family may be neutropenic, not all are affected by recurrent infections or periodontal disease (34). These findings might be explained by the variable genetic expression of the disorder or by the variable effects of the environment (such as plaque or smoking) on these patients.…”
Section: Evidence For the Role Of Genetic Variants In Periodontitismentioning
confidence: 99%
“…Oral manifestations of chronic benign neutropenia include hyperplastic, edematous, and fiery‐red gingiva with areas of desquamation (6). Deasy described a 14‐year‐old boy with chronic benign neutropenia who was referred due to severe gingival inflammation, hyperplastic papillae, isolated areas of gingival recession, and a molar furcal lesion (51). Reichart et al.…”
Section: Chronic Neutropeniasmentioning
confidence: 99%
“…Deasy et al 20 described a family exhibiting familial benign chronic neutropenia. They showed that, although several individuals within this family were neutropenic, not all were affected either by recurrent infections or by inflammatory periodontal disease.…”
Section: Quantitative Leucocyte Disorders Neutropeniamentioning
confidence: 99%